Pengaruh Disiplin Kerja dan Kompetensi Terhadap Kepuasan Kerja Pegawai Pada Dinas Komunikasi Informatika dan Statistik Kabupaten Bima - Muh. Abie Nasution; Firmansyah Kusumayadi (JUMABI: Jurnal Manajemen, Akuntansi dan Bisnis, 2025)
This study aims to determine whether work discipline competence has a positive and significant effect on employee job satisfaction at the Communication, Informatics and Statistics Office of Bima Regency. The instrument in the study used a questionnaire with a Likert scale. The population in this study was 59 employees consisting of 36 Civil Servants, 2 Government Employees with Work Agreements, 5 Honorary employees and 16 volunteers. The sample in this study was 38 Civil Servants and Government Employees with Work Agreements with the sampling technique used, namely purposive sampling technique. Data collection techniques used observation, questionnaires, documentation. Data analysis techniques used validity tests, reliability tests, multiple linear regression tests, classical assumption tests, correlation coefficient tests, determination coefficients, t tests and f tests with the help of spss version 23 forwindows. The results of the study indicate that there is a significant positive partial influence of work discipline on employee job satisfaction, there is a positive and significant partial influence of competence on employee job satisfaction, there is a positive and significant simultaneous influence of work discipline and competence on employee job satisfaction at the Communication, Informatics and Statistics Service of Bima Regency.